Nasopharyngeal carriage, serotype, antimicrobial susceptibility, and genotype of pneumococci in young healthy children attending daycare centres in Klang Valley, Malaysia - Mohamad, Norfazlina; Meor Yahaya, Maitasha Alia; Muthanna, Abdul Rahman; Mohd Desa, Mohd Nasir; Ismail, Elysha Nur; Dapari, Rahmat; Abd Rahman, Anita; Hasan, Ahmad Najib; Mohd Taib, Niazlin; Masri, Siti Norbaya; Chee, Hui Yee; Rengasamy, Sithra; et al. (Elsevier, 2025)
Objective: Implementation of pneumococcal conjugate vaccines (PCV) targeting selected serotypes has led to a decrease in invasive pneumococcal diseases. In Malaysia, PCV10 was recently included in the national immunisation programme. Therefore, monitoring serotype distribution and antimicrobial resistance of pneumococci in high-density areas is crucial. This study investigated the serotype distribution, antimicrobial resistance pattern, and genotype of pneumococci in healthy children below 5 years old attending daycare centres in Klang Valley, Malaysia, while indirectly assessing transmission dynamics through nasopharyngeal carriage. Methods: 168 children across 25 daycare centres provided parental consent. Nasopharyngeal swabs collected between January 2023 and May 2024, were analysed for pneumococcal carriage, and serotyped by PCR. Antimicrobial susceptibility was determined using E-test assay. Multilocus sequence typing was performed on isolates with reduced susceptibility. Results: The pneumococcal carriage rate was 22.6%. Serotype 15C was the most prevalent (15.8%), followed by 23A and 11A. In the E-test assay, 47.4% isolates were resistant to erythromycin, 28.9% to tetracycline, and 5.3% to penicillin. One isolate was resistant to ceftriaxone, whereas none demonstrated resistance to cefotaxime; reduced susceptibility to the two antibiotics was observed in one isolate, while two others had intermediate susceptibility to either ceftriaxone or cefotaxime alone. Sequence type distribution was diverse, with ST338 being the most common (n = 3). Conclusions: The predominance of nonvaccine serotypes, particularly 15C and 23A, alongside antibiotic resistance, indicates a potential epidemiological shift in the post-PCV era. These results emphasise the need for continuous surveillance to monitor serotype dynamics and antimicrobial resistance pattern in the community.